Spatio-Temporal Distribution of Monarch Butterflies Along Their Migratory Route - Castañeda, Saul; Botello, Francisco; Sánchez-Cordero, Víctor; Sarkar, Sahotra (Frontiers in Ecology and Evolution, 2019)
Efforts to conserve the migratory phenomenon of monarch butterflies in eastern North America have increased since a 2013-2014 monitoring report documenting a historical population low at the Monarch Butterfly Biosphere Reserve in Mexico. Surprisingly, there have been few systematic attempts to develop predictive models of monarch butterfly distributions along their migratory route between Mexico and the United States and Canada. Here we produced monthly habitat suitability models for monarch butterflies along their migratory route to identify potential areas for resting, feeding, and reproduction of the population. We compiled a point occurrence database of monarch butterflies for Mexico, USA, and Canada, including georeferenced records from GBIF, the Naturalista platform in Mexico, Correo Real initiative, and the Mexican governmental monitoring network for the monarch butterfly. We produced monthly habitat suitability models (HSM), using the R language and environment for statistical computing, abiotic (WorldClim), edaphic, and topographic variables. A total of 95 HSM were produced for each month. June to September, corresponding to the reproduction months in North America showed the highest geographic extent with suitable habitats; April, corresponding to the reproduction of the first post-migration generation, showed the smallest area. September, October and November, correspond to the movement of the monarch butterflies southwards, showed typical recognized distribution of the phenomenon and the overwintering months. December to February showed the smallest geographic extent in habitat suitability. Edaphic variables ranked high in importance in HSM for 11 of 12 months, indicating the relevance of vegetation and floral resources in the monarch butterfly migration route. Identifying such regions contribute to establish concrete conservation programs accordingly, as reduction of the use of pesticides and herbicides, decrease in the speed of cars in roads, and planting species with high nectary value, among others.. Our study provides a first predictive spatio-temporal approximation of the monarch butterfly migratory route annual cycle..